Pendekatan Psikologi Manajemen untuk Meningkatkan Efektivitas Pembelajaran dan Kinerja Pendidik - Siti Ma’unatul Afifah; Alya Rahmawati; Yova Hamdani; Mualip Mualip; Salisa Indah Aini; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study examines the application of management psychology approach as a strategy to improve the effectiveness of learning and performance of educators in Indonesia. Using descriptive-analytical qualitative methods, this study explores how factors such as work motivation, leadership, and stress management contribute to creating a conducive educational environment. Literature analysis and empirical findings reveal that increasing educator motivation through rewards, feedback-based evaluation, and the implementation of transformational and participatory leadership can significantly increase work enthusiasm and innovation in the learning process. In addition, balanced workload management and the provision of work welfare programs have been shown to help reduce stress levels and improve the psychological well-being of educators. The results of this study provide recommendations for educational institutions to integrate the principles of management psychology into human resource management policies in order to achieve continuous improvement in the quality of teaching and learning.